Induction of systemic resistance in Chinese cabbage against black rot by plant growth-promoting rhizobacteria - Liu, Ke; Garrett, Carol; Fadamiro, Henry; Kloepper, Joseph W. (Biological control, 2016)
[Display omitted] •Plant growth-promoting rhizobacteria induced systemic resistance to black rot.•Two mixtures of strains were formed for biocontrol of black rot.•The marketable yield was increased by individual strains and mixtures of strains. Black rot, caused by Xanthomonas campestris pv. campestris, is the most important and potentially destructive disease of cabbage. The objectives of this study were to select plant growth-promoting rhizobacteria (PGPR) strains and to form strain mixtures with the capacity to elicit induced systemic resistance or to increase plant growth in Chinese cabbage. In preliminary screening, 10 of 12 tested individual PGPR strains (AP136, AP188, AP209, AP213, AP217, AP218, AP219, AP282, AP295, and AP305) reduced the number of foliar lesions, and 2 PGPR strains (AP7 and AP18) increased all tested parameters of plant growth promotion, including shoot fresh weight, shoot dry weight, root fresh weight, root dry weight and plant diameter. In advanced tests, four individual stains (AP136, AP209, AP282 and AP305) were combined into mixture-1. Mixture-2 contained all strains in mixture-1 plus three additional stains (AP7, AP18 and AP218). Both mixtures and three individual strains (AP136, AP209 and AP305) significantly reduced the number of black rot lesions, and mixture-2 increased shoot dry weight and root dry weight in greenhouse tests. In a field test, all the tested treatments significantly reduced disease incidence on whole plants at three weeks after transplanting and reduced head disease severity at harvest time. All treatments also increased marketable yield compared to the nonbacterized control. These results demonstrated that specific individual PGPR strains and strain mixtures induced systemic resistance to black rot in the greenhouse and field.